Precipitation of Calcium Phosphates in the Presence of Collagen Type I on Four Different Bioactive Titanium Surfaces: an in Vitro Study - Victoria F. Stenport; Julia Olander; Per Kjellin; Fredrik Currie; Young-Taeg Sul; Anna Arvidsson (Stilus Optimus, 2015)
Objectives: To compare the properties of calcium phosphate precipitation on four different bioactive surface preparations and one control surface in the simulated body fluid model with added collagen type I. Material and Methods: Blasted titanium discs were treated with four different surface modifications, alkali and heat, sodium fluoride, anodic oxidation and hydroxyapatite coating. The discs were divided into five groups where one group, the blasted, served as control. The discs were immersed in simulated body fluid and collagen for 24 h, 3 days, 1 week and 2 weeks and then analysed by optical interferometry, scanning electron microscopy/energy dispersive X-ray analysis and X-ray photoelectron spectroscopy. Results: All surfaces show small precipitates after 3 days which with longer immersion times increase. After 2 weeks the surfaces were completely covered with precipitates, and Ca/P ratios were approximately 1.3, independently on surface preparation. The fluoridated discs showed significantly (P ≤ 0.05) higher degree of CaP after one week of immersion as compared to the other surface preparations. The collagen type I content increased with time, as reflected by increased nitrogen content. Conclusions: The results from this study indicate that a fluoridated titanium surface may favour precipitation of calcium phosphate in the presence of collagen type I, as compared to the other surface treatments of the present study.